Reactive adhesives, laminates and packaging

JP7639301B2Active Publication Date: 2025-03-05TOYO INK MFG CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020179421
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-27
Publication Date
2025-03-05
Estimated Expiration
2040-10-27

AI Technical Summary

Benefits of technology

【0014】 本発明により、シランカップリング剤を用いなくても接着強度に優れ、特にニトロセルロース樹脂をバインダー成分とするインキを用いた場合においても良好な接着強度を示し、さらに、高速塗工において塗工ムラが発生せず、残留溶剤が少ない反応性接着剤、並びに、該接着剤を用いた、接着力に優れ且つ外観良好な積層体及び包装体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639301000001
    Figure 0007639301000001
Patent Text Reader

Abstract

To provide a reactive adhesive which is excellent in adhesive strength without using a silane coupling agent, exhibits a good adhesive strength even when ink containing a nitrocellulose resin as a binder component is used, prevents coating unevenness in high-speed coating, and has a reduced residual solvent content, and a laminate and a package using the adhesive which are excellent in adhesive force and have good appearance.SOLUTION: A reactive adhesive contains polyol containing polyether urethane polyol (A) and polyester polyol (B) having an acid value of 10-50 mgKOH / g, a hydroxy acid having two carboxy groups and polyisocyanate, in which the content of the polyester polyol (B) is 1.0-5.0 pts.mass with respect to 100 pts.mass of the polyether urethane polyol (A).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reactive adhesive composition, and a laminate and a packaging material using said adhesive, and more specifically, to an adhesive useful as a packaging material for foods, medical products, cosmetics, etc., and a laminate and a packaging material using said adhesive. [Background technology]

[0002] Laminates formed by bonding various plastic films together or a plastic film and a metal-deposited film or metal foil via an adhesive layer are used as flexible packaging materials for packaging contents such as food, medical products, cosmetics, etc. Hydroxyl / isocyanate-based two-liquid curing urethane adhesives are widely used as adhesives for forming the adhesive layer, but in recent years, the use of films with low surface treatment has been increasing from the viewpoint of cost reduction, and there is a demand for further improvement in the adhesive strength of adhesives to plastic films, metal-deposited films, or metal foils. For example, adhesives using polyester polyols are known as adhesives with excellent adhesive strength and heat resistance. However, since polyester polyols have high affinity with diluting solvents and poor solvent removal properties, when such polyester polyols are used as the main resin, problems such as poor appearance and residual solvent occur in high-speed coating at 200 m / min or more. On the other hand, for example, Patent Documents 1 and 2 disclose that an adhesive using polyether urethane polyol suppresses the degree of viscosity increase and has excellent coatability and residual solvent. However, adhesives using polyether urethane polyol have the problem that their adhesion to metals and adhesive strength are significantly reduced when ink containing nitrocellulose resin (nitrocellulose) as a binder component is used. Moreover, in recent years, there has been growing interest in the hygiene aspects of food ingredients, particularly in Europe, and as a result, efforts are being made to reduce the use of silane coupling agents, which have been used to improve heat resistance and metal adhesion. However, with conventional methods, it has not been possible to obtain an adhesive that has good coatability and residual solvent during high-speed coating without using a silane coupling agent, and that also has excellent adhesive strength when used with an ink that contains nitrocellulose resin as a binder component. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-306931 A [Patent Document 2] JP 2006-306932 A Summary of the Invention [Problem to be solved by the invention]

[0004] Therefore, an object of the present invention is to provide a reactive adhesive that has excellent adhesive strength even without the use of a silane coupling agent, and that exhibits particularly good adhesive strength even when used with an ink containing a nitrocellulose resin as a binder component, and that does not cause coating unevenness in high-speed coating and has little residual solvent, as well as a laminate and package that use this adhesive and have excellent adhesive strength and good appearance. [Means for solving the problem]

[0005] As a result of extensive research, the inventors discovered that the above-mentioned problems could be solved by combining a specific polyester polyol in a prescribed range amount and a hydroxy acid having two carboxy groups with a polyether urethane polyol, thereby completing the present invention.

[0006] The present invention relates to a reactive adhesive comprising a polyol containing a polyetherurethane polyol (A) and a polyester polyol (B) having an acid value of 10 to 50 mgKOH / g, a hydroxy acid having two carboxy groups, and a polyisocyanate, wherein the content of the polyester polyol (B) is 1.0 to 5.0 parts by mass per 100 parts by mass of the polyetherurethane polyol (A).

[0007] The present invention relates to the above reactive adhesive, wherein the polyetherurethane polyol (A) has a weight average molecular weight of 5,000 to 35,000.

[0008] The present invention relates to the reactive adhesive, wherein the content of the hydroxy acid having two carboxy groups is 0.1 to 1.5 parts by mass per 100 parts by mass of the polyetherurethane polyol (A).

[0009] The present invention relates to the reactive adhesive, wherein the hydroxy acid having two carboxy groups comprises an aliphatic hydroxy acid having 3 to 10 carbon atoms.

[0010] The present invention relates to the above reactive adhesive, wherein the polyester polyol (B) has a number average molecular weight of 500 to 3,000.

[0011] The present invention relates to the above reactive adhesive, wherein the polyisocyanate comprises a polyether urethane polyisocyanate which is the reaction product of an aromatic diisocyanate and a polyether polyol.

[0012] The present invention relates to a laminate having a layer of the above-mentioned reactive adhesive between a first substrate and a second substrate.

[0013] The present invention relates to a package using the above laminate. Effect of the Invention

[0014] The present invention makes it possible to provide a reactive adhesive which has excellent adhesive strength even without the use of a silane coupling agent, and which exhibits particularly good adhesive strength even when used with an ink containing a nitrocellulose resin as a binder component, and which does not cause coating unevenness in high-speed coating and has little residual solvent, as well as a laminate and package which use this adhesive and have excellent adhesive strength and good appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] <Reactive adhesive> The reactive adhesive of the present invention is an adhesive that hardens through a chemical reaction between an isocyanate group and a hydroxyl group, and is characterized by comprising a polyol including a polyether urethane polyol (A), a polyester polyol (B) having an acid value of 10 to 50 mgKOH / g in a predetermined range, a hydroxy acid having two carboxy groups, and a polyisocyanate. In laminates such as packaging materials, there is a problem that the nitrocellulose and additives contained in the ink layer permeate from the ink layer into the adhesive layer and migrate to the interface between the adhesive layer and the substrate, resulting in a decrease in adhesive strength over time. However, by combining a polyester polyol (B) having a specific amount of acid value of 10 to 50 mgKOH / g and a hydroxy acid having two carboxy groups with a polyether urethane polyol, the bond length of the polyether urethane, which is prone to migration, is controlled, and the acid groups such as the carboxy group capture the additives, and the hydroxy acid having two carboxy groups acts as a bridge between the adhesive layer and the substrate without being affected by the ink components, thereby demonstrating excellent adhesive strength. As a result, the reactive adhesive of the present invention suppresses coating unevenness and has little residual solvent even when applied at high speeds, and furthermore, it is possible to obtain an adhesive with excellent adhesive strength when used with ink containing nitrocellulose resin as a binder component, even without the use of a silane coupling agent. The present invention will be described in detail below.

[0016] <Polyol> The polyol in the present invention contains a polyetherurethane polyol (A) and 1.0 to 5.0 parts by mass of a polyester polyol (B) having an acid value in the range of 10 to 50 mgKOH / g, relative to 100 parts by mass of the polyetherurethane polyol (A). It is important that the content of polyester polyol (B) is in the range of 1.0 to 5.0 parts by mass. If it is less than 1.0 part by mass, the adhesive strength is insufficient when using an ink containing nitrocellulose resin as a binder component, and if it exceeds 5.0 parts by mass, high-speed coating properties are reduced. The content of polyester polyol (B) is more preferably 2.0 to 4.0 parts by mass per 100 parts by mass of polyether urethane polyol (A). If it is in the range of 2.0 to 4.0 parts by mass, it is preferable because it is more excellent in adhesive strength and residual solvent.

[0017] [Polyether urethane polyol (A)] The polyether urethane polyol is preferably a compound having a hydroxyl group and a urethane bond, which is a reaction product of a polyether polyol and a polyisocyanate under a condition of excess hydroxyl group. These polyether urethane polyols may be used alone or in combination of two or more.

[0018] The polyether polyol may be any compound having two or more hydroxyl groups and two or more ether bonds in the molecule. Examples of polyether polyols include polyalkylene glycols such as polyethylene glycol, polytrimethylene glycol, polypropylene glycol, polytetramethylene glycol, and polybutylene glycol; polyethylene glycol / polypropylene glycol block copolymers; and propylene oxide / ethylene oxide random polyethers. In addition, an addition polymer obtained by addition polymerization of an oxirane compound such as ethylene oxide, propylene oxide, butylene oxide, or tetrahydrofuran to a low molecular weight polyol initiator such as water, ethylene glycol, propylene glycol, trimethylolpropane, glycerin, sorbitol, or sucrose may be used as the polyether polyol. Examples of the addition polymer include propylene glycol propylene oxide adducts, glycerin propylene oxide adducts, sorbitol-based propylene oxide adducts, and sucrose-based propylene oxide adducts.

[0019] The number average molecular weight of the polyether polyol is preferably from 100 to 5000, and more preferably from 300 to 2500. These polyether polyols may be used alone or in combination of two or more.

[0020] The polyisocyanate may be any compound having two or more isocyanate groups. Examples of the polyisocyanate include aromatic polyisocyanates, araliphatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates, and modified products thereof may also be used. These polyisocyanates may be used alone or in combination of two or more.

[0021] Examples of the aromatic polyisocyanate include aromatic diisocyanates such as diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, phenylene diisocyanate, tolylene diisocyanate, and naphthalene diisocyanate; and aromatic polyisocyanates such as polymethylene polyphenyl polyisocyanate. Examples of the araliphatic polyisocyanate include araliphatic diisocyanates such as 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or a mixture thereof. Examples of the aliphatic polyisocyanate include aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, 2,6-diisocyanate methyl caproate, lysine diisocyanate, and dimer acid diisocyanate. Examples of alicyclic polyisocyanates include alicyclic diisocyanates such as 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, isophorone diisocyanate, 4,4'-methylene bis(cyclohexyl isocyanate), methyl 2,4-cyclohexane diisocyanate, methyl 2,6-cyclohexane diisocyanate, 1,4-bis(isocyanate methyl)cyclohexane, 1,3-bis(isocyanate methyl)cyclohexane, and norbornene diisocyanate.

[0022] Examples of modified polyisocyanates include allophanate-type modified products, isocyanurate-type modified products, biuret-type modified products, and adduct-type modified products.

[0023] The polyether urethane polyol (A) is preferably a reaction product of a difunctional or trifunctional polyalkylene glycol having a number average molecular weight of 100 to 5,000 and an aromatic diisocyanate. The weight average molecular weight of the polyether urethane polyol (A) is preferably 5,000 to 35,000.

[0024] The polyetherurethane polyol (A) in the present invention may be modified, or may be a polyetherurethane polyol having a carboxyl group introduced therein by reacting the polyetherurethane polyol with an acid anhydride. Examples of the acid anhydride include pyromellitic anhydride, mellitic anhydride, trimellitic anhydride, and trimellitic ester anhydride. Examples of the trimellitic ester anhydride include ester compounds obtained by esterifying an alkylene glycol or alkanetriol having 2 to 30 carbon atoms with trimellitic anhydride, and specific examples thereof include ethylene glycol bisanhydrotrimellitate, propylene glycol bisanhydrotrimellitate, and the like.

[0025] [Polyester polyol (B) having an acid value of 10 to 50 mgKOH / g] The polyester polyol (B) can be selected from known polyester polyols as long as the acid value is within the range of 10 to 50 mgKOH / g. One type may be used alone, or two or more types may be used in combination.

[0026] Examples of the polyester polyol (B) include polyester polyols obtained by reacting a carboxyl group component with a hydroxyl group component; and polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone). Examples of the carboxyl group component include dibasic acids such as terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, phthalic anhydride, adipic acid, azelaic acid, sebacic acid, succinic acid, glutaric acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, maleic anhydride, and itaconic anhydride, or dialkyl esters thereof, or mixtures thereof. Examples of the hydroxyl group component include ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, butylene glycol, neopentyl glycol, Examples of the diols include dineopentyl glycol, trimethylolpropane, glycerin, 1,6-hexanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, 1,9-nonanediol, polyoxyethylene glycol, polyoxypropylene glycol, polytetramethylene ether glycol, polyether polyol, polycarbonate polyol, polyolefin polyol, acrylic polyol, polyurethane polyol, and other diols or mixtures thereof. These carboxyl group components and hydroxyl group components may each be used alone or in combination of two or more.

[0027] The polyester polyol (B) may be a polyester urethane polyol reacted with a diisocyanate, such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, hexamethylene diisocyanate, or hydrogenated diphenylmethane diisocyanate.

[0028] It is also important that the polyester polyol (B) of the present invention has an acid value in the range of 10 to 50 mgKOH / g. An acid value of 10 mgKOH / g or more exhibits excellent adhesive strength to inks containing nitrocellulose resin as a binder component, while an acid value of 50 mgKOH / g or less exhibits excellent suitability for high-speed coating. The acid value of the polyester polyol (B) is preferably from 20 to 50 mgKOH / g, and more preferably from 20 to 30 mgKOH / g. When the polyester polyol (B) contains a plurality of polyester polyols, the acid value of the polyester polyol (B) can be determined from the acid value of each polyester polyol and the mass ratio thereof.

[0029] From the viewpoint of having an acid value, the polyester polyol (B) is preferably one into which a carboxyl group has been introduced by reacting with an acid anhydride. Examples of the acid anhydride include pyromellitic anhydride, mellitic anhydride, trimellitic anhydride, and trimellitic ester anhydride. Examples of the trimellitic ester anhydride include ester compounds obtained by esterifying an alkylene glycol or alkanetriol having 2 to 30 carbon atoms with trimellitic anhydride, and specific examples thereof include ethylene glycol bisanhydrotrimellitate, propylene glycol bisanhydrotrimellitate, and the like.

[0030] The polyester polyol (B) is more preferably an acid anhydride modified product obtained by reacting a part of the hydroxyl groups of a polyester polyol obtained by reacting a carboxyl group component with a hydroxyl group component with an acid anhydride, and the hydroxyl group component preferably contains 30 to 70 mol % of 1,4-butanediol in 100 mol of the total hydroxyl group components. By using such a polyester polyol, an adhesive composition having excellent adhesive strength, no coating unevenness even in high-speed coating, and little residual solvent can be obtained.

[0031] The number average molecular weight of the polyester polyol (B) is not particularly limited, but is preferably 500 to 3,000, and more preferably 1,000 to 2,500. In this specification, the number average molecular weight and weight average molecular weight are values ​​measured using GPC (gel permeation chromatography) manufactured by Showa Denko KK, using tetrahydrofuran as a solvent, and converted into standard polystyrene. When polyester polyol (B) contains multiple polyester polyols in order to satisfy various physical properties required for the packaging material, the number average molecular weight of polyester polyol (B) can be determined from the number average molecular weights of each polyester polyol and their mass ratios.

[0032] [Other polyols] The polyol component in the present invention may contain other polyols than the polyether urethane polyol (A) and the polyester polyol (B) as long as the effects of the present invention are not impaired. Examples of other polyols that may be contained include polyester polyols or polyester urethane polyols having an acid value of less than 10 mgKOH / g, polyester polyols or polyester urethane polyols having an acid value of more than 50 mgKOH / g, polycarbonate polyols, polycaprolactone polyols, polyether polyols, polyolefin polyols, acrylic polyols, silicone polyols, castor oil-based polyols, and fluorine-based polyols. Polyols may also be acid-modified products in which some of the hydroxyl groups in the polyol have been modified with an acid. These other polyols may be used alone or in combination of two or more.

[0033] <Hydroxy acid with two carboxy groups> The hydroxy acid in the present invention may be any compound having two carboxy groups and one or more hydroxyl groups in the molecule, and may be selected from known hydroxy acids. By using such a hydroxy acid, one carboxy group is bonded to the surface of the substrate, and the other carboxy group is bonded to the adhesive, forming a bridge at the interface between the adhesive layer and the substrate. Furthermore, the carboxy group captures the migration components in the ink. This allows the adhesive strength to be improved without being affected by the components of the ink.

[0034] Examples of hydroxy acids having two carboxy groups include aliphatic hydroxy acids, which are not particularly limited, but include, for example, malic acid, tartaric acid, citric acid, isocitric acid, and the like, and may be isomers thereof. The hydroxy acid in the present invention is preferably an aliphatic hydroxy acid, more preferably having 3 to 10 carbon atoms, and further preferably having 3 to 8 carbon atoms. These hydroxy acids may be used alone or in combination of two or more.

[0035] The content of the hydroxy acid is preferably 0.1 to 1.5 parts by mass, more preferably 0.1 to 1.0 parts by mass, and even more preferably 0.2 to 0.8 parts by mass, based on 100 parts by mass of the polyether urethane polyol (A). A range of 0.1 to 1.5 parts by mass is preferable because it achieves both pot life and adhesive strength, and provides excellent high-speed coatability and adhesive strength.

[0036] <Polyisocyanate> The polyisocyanate in the present invention may be any compound having two or more isocyanate groups, and may be selected from known polyisocyanates. Examples of polyisocyanates include aromatic polyisocyanates, araliphatic polyisocyanates, aliphatic polyisocyanates, alicyclic polyisocyanates, and modified products thereof. These polyisocyanates may be used alone or in combination of two or more. For the aromatic polyisocyanates, araliphatic polyisocyanates, aliphatic polyisocyanates, alicyclic polyisocyanates, and modified products thereof, the explanation of the polyisocyanates in the section on polyether urethane polyol (A) can be applied.

[0037] The polyisocyanate in the present invention is preferably a modified polyisocyanate obtained by reacting the above-mentioned polyisocyanate with a polyol under conditions of an excess of isocyanate groups, and includes a reaction product having an isocyanate group and a urethane bond. The polyol that forms the modified product of the polyisocyanate is not particularly limited and can be selected from known polyols, and examples thereof include polyester polyols, polyester urethane polyols, polycarbonate polyols, polycaprolactone polyols, polyether polyols, polyether urethane polyols, polyolefin polyols, acrylic polyols, silicone polyols, castor oil-based polyols, and fluorine-based polyols.

[0038] From the viewpoint of laminate strength, the polyisocyanate is more preferably a reaction product of the above-mentioned polyisocyanate with a polyether polyol, and further preferably a polyether urethane polyisocyanate which is a reaction product of an aromatic diisocyanate with a polyether polyol. For the aromatic diisocyanate and polyether polyol, the explanations of the polyisocyanate and polyether polyol in the section on polyether urethane polyol (A) can be applied.

[0039] The weight average molecular weight of the polyisocyanate is preferably 5,000 to 30,000.

[0040] <Solvent> The adhesive of the present invention can be used as a solvent-based or solventless adhesive, and may contain a solvent as necessary. Note that the "solvent" in the present invention refers to an organic solvent that has high solubility and can dissolve the polyol or polyisocyanate of the present invention. Examples of the organic solvent having high solubility include toluene, xylene, methylene chloride, tetrahydrofuran, methanol, ethanol, isopropyl alcohol, methyl acetate, ethyl acetate, n-butyl acetate, acetone, methyl ethyl ketone, cyclohexanone, toluene, xylol, n-hexane, and cyclohexane. More preferred organic solvents are those which are inactive to polyisocyanates, and examples thereof include esters such as ethyl acetate, ketones such as methyl ethyl ketone, and aromatic hydrocarbons such as toluene and xylene.

[0041] The viscosity of the adhesive of the present invention is preferably 100 to 10,000 mPa·s, more preferably 100 to 5,000 mPa·s, at room temperature to 150° C., and even more preferably 100 to 10,000 mPa·s, more preferably 100 to 5,000 mPa·s, at room temperature to 100° C. When the viscosity is 100 to 5,000 mPa·s at room temperature to 100° C., it can be used as a solventless adhesive. If the viscosity of the adhesive is higher than the above range, it may be diluted with the above organic solvent. The content of the organic solvent depends on the required viscosity, but it is generally desirable to include the organic solvent in the range of 15 to 60 mass % relative to the resin.

[0042] The adhesive of the present invention is a reactive urethane-based adhesive obtained by blending a polyol, a hydroxy acid having two carboxy groups, and a polyisocyanate, and the blending amount of the polyisocyanate is preferably in the range of 10 to 250 mass %, more preferably in the range of 50 to 200 mass %, and even more preferably in the range of 50 to 100 mass %, based on the polyol.

[0043] The blending ratio of the polyol and the polyisocyanate is preferably such that the equivalent ratio [NCO / OH] of the total isocyanate groups contained in the isocyanate to the total hydroxyl groups contained in the polyol is in the range of 1.1 to 5.0, more preferably 1.3 to 2.5.

[0044] The adhesive of the present invention preferably has an acid value of 1 mgKOH / g or less, more preferably 0.5 mgKOH / g or less immediately after mixing the polyol, the hydroxy acid having two carboxy groups, and the polyisocyanate.

[0045] [Other ingredients] The adhesive of the present invention may contain other components other than the polyol, the hydroxy acid having two carboxy groups, and the polyisocyanate in order to satisfy various physical properties required for the adhesive or packaging material. These other components may be blended with either the polyol or the polyisocyanate, or may be added when blending the polyol and the polyisocyanate. These other components may be used alone or in combination of two or more.

[0046] (Phosphorus oxygen acid or its derivatives) The adhesive of the present invention may further contain a phosphorus oxyacid or a derivative thereof in order to enhance acid resistance. Among the phosphorus oxyacids or derivatives thereof, the phosphorus oxyacid may be any one having at least one free oxyacid, and examples thereof include phosphoric acids such as hypophosphorous acid, phosphorous acid, orthophosphoric acid, and hypophosphoric acid; and condensed phosphoric acids such as metaphosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, polyphosphoric acid, and ultraphosphoric acid. In addition, examples of derivatives of phosphorus oxyacids include those partially esterified with alcohols in a state in which at least one free oxyacid remains. Examples of these alcohols include aliphatic alcohols such as methanol, ethanol, ethylene glycol, and glycerin; and aromatic alcohols such as phenol, xylenol, hydroquinone, catechol, and phloroglucinol. The amount of phosphorus oxyacid or a derivative thereof added is preferably 0.01 to 10% by mass, more preferably 0.05 to 5% by mass, and even more preferably 0.1 to 1% by mass, based on the solid content of the adhesive.

[0047] (Leveling agent or defoamer) The adhesive of the present invention may further contain a leveling agent or a defoaming agent in order to improve the appearance of the laminate. Examples of the leveling agent include polyether-modified polydimethylsiloxane, polyester-modified polydimethylsiloxane, aralkyl-modified polymethylalkylsiloxane, polyester-modified hydroxyl-containing polydimethylsiloxane, polyetherester-modified hydroxyl-containing polydimethylsiloxane, acrylic copolymer, methacrylic copolymer, polyether-modified polymethylalkylsiloxane, acrylic acid alkyl ester copolymer, methacrylic acid alkyl ester copolymer, and lecithin. Examples of the defoaming agent include silicone resin, silicone solution, and copolymers of alkyl vinyl ether, alkyl acrylate, and alkyl methacrylate.

[0048] (Reaction accelerator) The adhesive of the present invention may further contain a reaction accelerator to promote the urethanization reaction. Examples of the reaction accelerator include metal catalysts such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, and dibutyltin dimaleate; tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7, 1,5-diazabicyclo(4,3,0)nonene-5,6-dibutylamino-1,8-diazabicyclo(5,4,0)undecene-7; and reactive tertiary amines such as triethanolamine.

[0049] The adhesive of the present invention may contain various additives within a range that does not impair the effects of the present invention. Examples of additives include inorganic fillers such as silica, alumina, mica, talc, aluminum flakes, and glass flakes, layered inorganic compounds, stabilizers (antioxidants, heat stabilizers, ultraviolet absorbers, hydrolysis inhibitors, etc.), rust inhibitors, thickeners, plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, fillers, crystal nucleating agents, and catalysts for adjusting the curing reaction.

[0050] The adhesive of the present invention is formed into a cured product by curing the adhesive at a temperature of 20° C. to 60° C. after bonding the objects to be adhered together. The adhesive is not particularly limited in its application, but is useful as an adhesive for laminating a plurality of substrates such as films to form a laminate.

[0051] <Laminates and packaging> The laminate of the present invention is obtained by laminating a layer of the reactive adhesive of the present invention between a first substrate and a second substrate, and specifically, when the reactive adhesive of the present invention is a solvent-based adhesive, it can be obtained by applying it to the first substrate using a dry laminator, optionally undergoing a drying step, laminating the second substrate to the applied surface, and curing the adhesive layer by aging. When the reactive adhesive is a solventless type, it can be obtained by using a non-solvent laminator, usually heating a roll coater to 30°C to 90°C, and using an adhesive with a viscosity of about 300 to 3000 mPa·s at 40°C after blending. The solid coating amount of the adhesive is preferably 0.5 to 6 g / m 2 More preferably, the solvent-free type has a coating weight of 1 to 3 g / m 2 , 1 to 5 g / m for solvent-based 2 The range is.

[0052] As the first substrate, a film-like substrate commonly used for packaging materials is preferable, and examples thereof include base films such as PET (polyethylene terephthalate) film, NY (nylon) film, OPP (biaxially oriented polypropylene) film, K-coat films such as polyvinylidene chloride, and various vapor-deposited films such as silica-deposited PET and alumina-deposited PET, and aluminum foil. As the second substrate, a film-like substrate that is generally used for packaging materials is preferable, and examples thereof include, in addition to the substrates listed as the first substrate, CPP (non-oriented polypropylene) film, sealant films such as LLDPE (linear low density polyethylene), LDPE (low density polyethylene), and HDPE (high density polyethylene), as well as aluminum-vapor-deposited or silica-vapor-deposited films of these.

[0053] Examples of the configuration of the laminate of the present invention include OPP / CPP, OPP / aluminum-vaporized CPP, nylon / CPP, NY / LLDPE, PET / CPP, PET / aluminum-vaporized CPP, PET / aluminum-vaporized PET / CPP, PET / aluminum-vaporized PET / LLDPE, PET / NY / CPP, alumina-vaporized PET / NY / CPP, PET / aluminum / LLDPE, NY / aluminum / LLDPE, PET / aluminum / CPP, NY / aluminum / CPP, silica-vaporized PET / NY / LLDPE, alumina-vaporized PET / NY / CPP, and PET / NY / PET / NY / aluminum / CPP, and an appropriate configuration can be selected depending on the application.

[0054] The laminate of the present invention may further have a pattern layer (hereinafter also referred to as a printed layer). The pattern layer is a layer on which any desired printed pattern such as letters, numbers, pictures, figures, symbols, patterns, etc. is formed for decoration, display of contents, display of expiration date, display of manufacturer, seller, etc., and for imparting aesthetics, and also includes a solid print layer. The pattern layer can be formed using a conventionally known pigment or dye, and the method of forming the pattern layer is not particularly limited. In general, the design layer is formed using an ink containing a colorant such as a pigment or dye and a binder resin. The binder resin contained in the ink is appropriately selected depending on the application and the substrate, and examples of the binder resin that can be used include polyurethane resin, polyurethane polyurea resin, vinyl chloride-acrylic acid ester copolymer, vinyl chloride-vinyl acetate copolymer, chlorinated polypropylene resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, polyamide resin, nitrocellulose resin (nitrocellulose), acrylic resin, polyester resin, alkyd resin, polyvinyl chloride resin, rosin resin, rosin-modified maleic acid resin, terpene resin, phenol-modified terpene resin, ketone resin, cyclized rubber, chlorinated rubber, butyral, petroleum resin, and modified resins thereof. The adhesive of the present invention has excellent adhesive strength, particularly when used with ink containing nitrocellulose resin as a binder component, and therefore exhibits even better adhesive strength in a configuration in which an adhesive layer is disposed on a design layer containing nitrocellulose resin.

[0055] The method for applying the ink is not particularly limited, and the ink can be applied by a method such as gravure coating, flexo coating, roll coating, bar coating, die coating, curtain coating, spin coating, inkjet coating, etc. The ink can be left as it is, or, if necessary, subjected to air blowing, heating, drying under reduced pressure, ultraviolet irradiation, etc., to form a printed layer. The design layer preferably has a thickness of 0.1 μm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less, and further preferably 1 μm or more and 3 μm or less.

[0056] The laminate of the present invention can be used mainly as a packaging material in the food, detergent, medicine, cosmetic and toiletry industries, and can also be used as a secondary package for packaging containers made of the packaging material. EXAMPLES

[0057] The present invention will be described in more detail below with reference to examples and comparative examples. In the examples and comparative examples, "parts" and "%" mean "parts by mass" and "% by mass" unless otherwise specified.

[0058] [Acid value (AV)] The acid value was measured by the following procedure. First, about 1 g of the sample (polyester polyol solution) was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added to dissolve it. Phenolphthalein test solution was added as an indicator and the solution was held for 30 seconds. After that, the solution was titrated with 0.1N alcoholic potassium hydroxide solution until it turned a pale pink color. The acid value was calculated by the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S Where S is the amount of sample taken (g) a: Amount of 0.1N alcoholic potassium hydroxide solution consumed (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution

[0059] [Hydroxyl value (OHV)] The hydroxyl value was measured by the following procedure. First, about 1 g of the sample (polyester polyol solution) was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added and dissolved. Then, exactly 5 ml of an acetylating agent (a solution in which 25 g of acetic anhydride was dissolved in pyridine to a volume of 100 ml) was added and stirred for about 1 hour. Phenolphthalein test solution was added as an indicator and allowed to stand for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a pale pink color. The hydroxyl value was calculated by the following formula (unit: mgKOH / g). Hydroxyl value (mgKOH / g) =[{(ba)×F×28.05} / S]+D Where S is the amount of sample taken (g) a: Amount of 0.1N alcoholic potassium hydroxide solution consumed (ml) b: Amount of 0.1N alcoholic potassium hydroxide solution consumed in the blank experiment (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution D: Acid value (mgKOH / g)

[0060] [Number average molecular weight (Mn), weight average molecular weight (Mw)] The number average molecular weight and weight average molecular weight were measured using a Showa Denko GPC (gel permeation chromatography) with a Shodex GPC LF-604 (Shodex) column and a GPC equipped with an RI detector (Shodex, GPC-104) using tetrahydrofuran as a solvent, and were calculated in terms of standard polystyrene.

[0061] [Residual solvent] The residual solvent amount was measured using a Shimadzu GC-8AFID type (hydrogen flame ionization detector) gas chromatography (column: 8G26-30 (3.0 m) made of glass, packing material: PEG-1500). 2 The laminate was cut into small pieces and placed in a 500 mL flask, sealed with silicone rubber, and heated at 80°C for 30 minutes. The flask was then removed from the oven and 1 mL was injected into a gas chromatograph using a gas-tight syringe. The residual solvent amount in the laminated sample was calculated using a calibration curve obtained in advance, and the results were expressed as mg / m 2 It was displayed as:

[0062] <Production of polyether urethane polyol (A)> (Synthesis Example 1) Polyether urethane polyol (A1) 12 parts of bifunctional polypropylene glycol with a number average molecular weight of about 2,000, 38 parts of bifunctional polypropylene glycol with a number average molecular weight of about 400, 3 parts of dipropylene glycol, and 18 parts of tolylene diisocyanate were charged into a reaction vessel, and the mixture was heated at 80-90°C for 3-5 hours while stirring under a nitrogen gas flow to carry out a urethane reaction. During the urethane reaction, 0.1% dibutyltin dilaurate (DBTDL) was added as a reaction catalyst to promote the reaction, and after the reaction was completed, a solution of polyether urethane polyol (A1) was obtained, which was diluted with ethyl acetate to adjust the non-volatile content to 75%. The viscosity of the solution was 4,500 mPa·s / 25°C, and the weight average molecular weight was 11,000.

[0063] (Synthesis Example 2) Polyether urethane polyol (A2) 8 parts of bifunctional polypropylene glycol with a number average molecular weight of about 2,000, 34 parts of bifunctional polypropylene glycol with a number average molecular weight of about 400, 3 parts of trifunctional polypropylene glycol with a number average molecular weight of about 400, 8 parts of tolylene diisocyanate, and 10 parts of 4,4'-diphenylmethane diisocyanate were charged into a reaction vessel, and the mixture was heated at 80-90°C for 3-5 hours while stirring under a nitrogen gas flow to carry out a urethane reaction. During the urethane reaction, 0.1% dibutyltin dilaurate was added as a reaction catalyst to promote the reaction, and after the reaction was completed, a solution of polyether urethane polyol (A2) was obtained, which was diluted with ethyl acetate to adjust the non-volatile content to 70%. The viscosity of the solution was 6,000 mPa·s / 25°C, and the weight average molecular weight was 22,000.

[0064] (Synthesis Example 3) Polyether polyurethane polyol (A3) Eight parts of bifunctional polypropylene glycol with a number average molecular weight of about 2,000, 36 parts of bifunctional polypropylene glycol with a number average molecular weight of about 400, 7 parts of trifunctional polypropylene glycol with a number average molecular weight of about 400, and 17 parts of tolylene diisocyanate were charged into a reaction vessel, and the mixture was heated at 80-90°C for 3-5 hours while stirring under a nitrogen gas flow to carry out a urethane reaction. During the urethane reaction, 0.1% dibutyltin dilaurate was added as a reaction catalyst to promote the reaction, and after the reaction was completed, a solution of polyether urethane polyol (A3) was obtained, which was diluted with ethyl acetate and adjusted to a non-volatile content of 70%. The viscosity of the solution was 7,000 mPa·s / 25°C. The weight average molecular weight was 32,000.

[0065] <Production of polyester urethane polyol> (Synthesis Example 4) Polyester urethane polyol (X1) 335 parts of isophthalic acid, 148 parts of sebacic acid, 134 parts of adipic acid, 83 parts of ethylene glycol, 143 parts of neopentyl glycol, and 157 parts of 1,6-hexanediol were charged and esterification reaction was carried out at 220 to 260 ° C. After a predetermined amount of water was distilled off, the pressure was gradually reduced and deglycolization reaction was carried out at 240 to 260 ° C. for 5 hours at 1.333 hPa or less to obtain a polyester polyol with a number average molecular weight of 6,000, a mass average molecular weight of 13,000, a hydroxyl value of 17 mg KOH / g, and an acid value of 0.5 mg KOH / g. Furthermore, 10 parts of isophorone diisocyanate was gradually added to the total amount of this polyester polyol and the reaction was carried out at 150 ° C. for about 2 hours to obtain a polyester urethane polyol with a number average molecular weight of 8,000, a weight average molecular weight of 20,000, a hydroxyl value of 12 mg KOH / g, and an acid value of 0.5 mg KOH / g. The obtained polyesterurethane polyol was diluted with ethyl acetate to obtain a solution of polyesterurethane polyol (X1) with a non-volatile content of 55%. The viscosity of the solution was 800 mPa·s / 25°C.

[0066] <Production of polyester polyol (B)> (Synthesis Example 5) Polyester polyol (B1) 325.8 parts of isophthalic acid, 286.5 parts of adipic acid, 158.2 parts of ethylene glycol, and 229.6 parts of 1,4-butanediol were charged, and esterification reaction was carried out at 200 to 230 ° C for 6 hours. After distillation of a predetermined amount of water, 0.01 parts of tetraisobutyl titanate was added, and the pressure was gradually reduced, and the mixture was heated at 20 to 30 hPa and 230 to 250 ° C for 6 hours to distill off a part of the glycol component, and an ester exchange reaction was carried out to obtain a polyester polyol. 30 parts of trimellitic anhydride were added to the total amount of this polyester polyol, and an acid-modified polyester polyol (B1) with a number average molecular weight of 2,000 and an acid value of 25 mg / KOH was obtained.

[0067] (Synthesis Example 6) Polyester polyol (B2) 325.8 parts of isophthalic acid, 286.5 parts of adipic acid, 158.2 parts of ethylene glycol, and 229.6 parts of 1,4-butanediol were charged, and esterification reaction was carried out at 200 to 230 ° C for 6 hours. After distillation of a predetermined amount of water, 0.01 parts of tetraisobutyl titanate was added, and the pressure was gradually reduced, and the mixture was heated at 20 to 30 hPa and 230 to 250 ° C for 6 hours to distill off a part of the glycol component, and an ester exchange reaction was carried out to obtain a polyester polyol. 35 parts of trimellitic anhydride were added to the total amount of this polyester polyol, and an acid-modified polyester polyol (B2) with a number average molecular weight of 1,800 and an acid value of 30 mg / KOH was obtained.

[0068] (Synthesis Example 7) Polyester polyol (B3) 325.8 parts of isophthalic acid, 286.5 parts of adipic acid, 158.2 parts of ethylene glycol, and 229.6 parts of 1,4-butanediol were charged, and esterification reaction was carried out at 200 to 230 ° C for 6 hours. After distillation of a predetermined amount of water, 0.01 parts of tetraisobutyl titanate was added, and the pressure was gradually reduced, and the mixture was heated at 20 to 30 hPa and 230 to 250 ° C for 6 hours to distill off a part of the glycol component, and an ester exchange reaction was carried out to obtain a polyester polyol. 45 parts of trimellitic anhydride were added to the total amount of this polyester polyol, and an acid-modified polyester polyol (B3) with a number average molecular weight of 2,200 and an acid value of 40 mg / KOH was obtained.

[0069] (Synthesis Example 8) Polyester polyol (B4) 325.8 parts of isophthalic acid, 286.5 parts of adipic acid, 158.2 parts of ethylene glycol, and 229.6 parts of 1,4-butanediol were charged, and esterification reaction was carried out at 200 to 230 ° C for 6 hours. After distillation of a predetermined amount of water, 0.01 parts of tetraisobutyl titanate was added, and the pressure was gradually reduced, and the mixture was heated at 20 to 30 hPa and 230 to 250 ° C for 6 hours to distill off a part of the glycol component, and an ester exchange reaction was carried out to obtain a polyester polyol. 55 parts of trimellitic anhydride were added to the total amount of this polyester polyol, and an acid-modified polyester polyol (B4) with a number average molecular weight of 1,800 and an acid value of 50 mg / KOH was obtained.

[0070] (Synthesis Example 9) Polyester polyol (B5) 325.8 parts of isophthalic acid, 286.5 parts of adipic acid, 158.2 parts of ethylene glycol, and 229.6 parts of 1,4-butanediol were charged, and esterification reaction was carried out at 200 to 230 ° C for 6 hours. After distillation of a predetermined amount of water, 0.01 parts of tetraisobutyl titanate was added, and the pressure was gradually reduced, and the mixture was heated at 20 to 30 hPa and 230 to 250 ° C for 6 hours to distill off a part of the glycol component, and an ester exchange reaction was carried out to obtain a polyester polyol. 12 parts of trimellitic anhydride were added to the total amount of this polyester polyol, and an acid-modified polyester polyol (B5) with a number average molecular weight of 2,400 and an acid value of 10 mg / KOH was obtained.

[0071] (Synthesis Example 10) Polyester polyol (B6) 325.8 parts of isophthalic acid, 286.5 parts of adipic acid, 158.2 parts of ethylene glycol, and 229.6 parts of 1,4-butanediol were charged, and esterification reaction was carried out at 200 to 230 ° C for 6 hours. After distillation of a predetermined amount of water, 0.01 parts of tetraisobutyl titanate was added, and the pressure was gradually reduced, and the mixture was heated at 20 to 30 hPa and 230 to 250 ° C for 6 hours to distill off a part of the glycol component, and an ester exchange reaction was carried out to obtain a polyester polyol. 6 parts of trimellitic anhydride were added to the total amount of this polyester polyol, and an acid-modified polyester polyol (B6) with a number average molecular weight of 2,000 and an acid value of 5 mg / KOH was obtained.

[0072] (Synthesis Example 11) Polyester polyol (B7) 325.8 parts of isophthalic acid, 286.5 parts of adipic acid, 158.2 parts of ethylene glycol, and 229.6 parts of 1,4-butanediol were charged, and esterification reaction was carried out at 200 to 230 ° C for 6 hours. After distillation of a predetermined amount of water, 0.01 parts of tetraisobutyl titanate was added, and the pressure was gradually reduced, and the mixture was heated at 20 to 30 hPa and 230 to 250 ° C for 6 hours to distill off a part of the glycol component, and an ester exchange reaction was carried out to obtain a polyester polyol. 70 parts of trimellitic anhydride were added to the total amount of this polyester polyol, and an acid-modified polyester polyol (B7) with a number average molecular weight of 1,500 and an acid value of 60 mg / KOH was obtained.

[0073] <Production of polyisocyanate> (Synthesis Example 12) Polyisocyanate (C1) 30 parts of bifunctional polypropylene glycol with a number average molecular weight of about 2,000, 6 parts of bifunctional polypropylene glycol with a number average molecular weight of about 400, 1 part of trifunctional trimethylolpropane, and 20 parts of 4,4'-diphenylmethane diisocyanate were charged into a reaction vessel, and the mixture was heated at 70-80°C for 4-7 hours while stirring under a nitrogen gas stream to carry out a urethane reaction. After the reaction was completed, the mixture was diluted with ethyl acetate to a non-volatile content of 75%, to obtain a solution of polyether urethane polyisocyanate (C1). The isocyanate group content of (C1) was 5.4%, and the viscosity was 1,500 mPa·s / 25°C.

[0074] (Synthesis Example 13) Polyisocyanate (C2) 23 parts of bifunctional polypropylene glycol with a number average molecular weight of about 2,000, 18 parts of bifunctional polypropylene glycol with a number average molecular weight of about 400, 2 parts of trifunctional polypropylene glycol with a number average molecular weight of about 400, and 30 parts of 4,4'-diphenylmethane diisocyanate were charged into a reaction vessel, and the mixture was heated at 70-80°C for 4-7 hours while stirring under a nitrogen gas flow to carry out a urethane reaction. After the reaction was completed, 7 parts of a trimethylolpropane adduct of tolylene diisocyanate was mixed in and diluted with ethyl acetate to a non-volatile content of 80%, to obtain a solution of polyether urethane polyisocyanate (C2). The isocyanate group content of (C2) was 4.8%, and the viscosity was 2,5000 mPa·s / 25°C.

[0075] (Synthesis Example 14) Polyisocyanate (C3) 35 parts of bifunctional polypropylene glycol with a number average molecular weight of about 2,000, 8 parts of bifunctional polypropylene glycol with a number average molecular weight of about 400, 2 parts of trifunctional polypropylene glycol with a number average molecular weight of about 400, and 20 parts of 4,4'-diphenylmethane diisocyanate were charged into a reaction vessel, and the mixture was heated at 70-80°C for 4-7 hours while stirring under a nitrogen gas stream to carry out a urethane reaction. After the reaction was completed, the mixture was diluted with ethyl acetate to a non-volatile content of 75%, to obtain a solution of polyether urethane polyisocyanate (C3). The isocyanate group content of (C3) was 3.6%, and the viscosity was 3,000 mPa·s / 25°C.

[0076] (Synthesis Example 15) Polyisocyanate (C4) A solution of polyisocyanate (C4) was obtained by mixing a trimethylolpropane adduct of 1,3-xylylene diisocyanate (XDI) and a trimethylolpropane adduct of isophorone diisocyanate (IPDI) in a solid ratio of 8:2 and adjusting the non-volatile content to 60% with ethyl acetate. The isocyanate group content of (C4) was 9.3%, and the viscosity was 150 mPa·s / 25℃.

[0077] <Production of reactive adhesives> [Examples 1 to 16, Comparative Examples 1 to 8] A polyol, a polyisocyanate, a hydroxy acid having two carboxy groups, and a silane coupling agent were mixed and stirred in the formulation shown in Table 1 to produce a reactive adhesive.

[0078] <Evaluation of reactive adhesives> The adhesive thus obtained was used to prepare the following laminates and evaluate them. The results are shown in Table 1.

[0079] [OPP / printing layer / adhesive layer / VMCPP composition] (Laminate (1-1)) Nitrocellulose / urethane ink, coating speed 200m / min Printing inks (Toyo Ink Co., Ltd., RV-R 16 red / 63 white, nitrocellulose / urethane ink) were each diluted with a solvent so that the viscosity was 20 seconds (25°C, Zahn cup No. 3). Corona-treated OPP film (Toyobo P-2161, thickness 20 μm) was printed with each diluted printing ink in the order of red, white, and red and white overlapping using a flexographic proofing 8-color press equipped with a solid plate. The printing speed was 50 m / min, and drying was performed at 50°C in each unit to obtain an OPP / printed layer laminate. The thickness of the printed layer was 1 μm. The adhesive obtained was applied to the printed layer of the obtained laminate using a laminator at a coating speed of 200 m / min, and the solvent was evaporated using a drying oven (70°C-80°C-80°C triple oven, oven length 2.0 m), after which the adhesive-coated surface was laminated with a VMCPP (Toray Film Processing Co., Ltd. 2703, thickness 25 μm, aluminum-vapor-deposited non-oriented polypropylene) film to obtain a laminate (1-1). The solid coating amount of the adhesive was 2.5 g / m 2 It was decided.

[0080] (Laminate (1-2)) Urethane ink, coating speed 200 m / min Printing inks (Toyo Ink Co., Ltd., Rio Alpha R39 indigo / R631 white, urethane ink) were each diluted with a mixed solvent so that the viscosity was 16 seconds (25°C, Zahn cup No. 3). Each diluted printing ink was printed on a corona-treated OPP film (Toyobo P-2161, thickness 20 μm) in the order of indigo, white, and indigo-white on top of each other using a gravure proofing two-color press equipped with a solid plate. The printing speed was 50 m / min, and drying was performed at 50°C in each unit to obtain an OPP / printed layer laminate. The thickness of the printed layer was 1 μm. The adhesive obtained was applied to the printed layer of the obtained laminate using a laminator at a coating speed of 200 m / min, and the solvent was evaporated using a drying oven (70°C-80°C-80°C triple oven, oven length 2.0 m), after which the adhesive-coated surface was laminated with a VMCPP (Toray Film Processing Co., Ltd. 2703, thickness 25 μm, aluminum-vapor-deposited non-oriented polypropylene) film to obtain a laminate (1-2). The solid coating amount of the adhesive was 2.5 g / m 2 It was decided.

[0081] (Laminate (1-3)) Nitrocellulose / urethane ink, coating speed 150m / min A laminate (1-3) was obtained in the same manner as for the laminate (1-1), except that the coating speed of the adhesive was changed from 200 m / min to 150 m / min.

[0082] (Laminate (1-4)) Nitrocellulose / urethane ink, coating speed 230m / min A laminate (1-4) was obtained in the same manner as for the laminate (1-1), except that the coating speed of the adhesive was changed from 150 m / min to 230 m / min.

[0083] [PET / printed layer / adhesive layer / aluminum / adhesive layer / LLDPE composition] (Laminate (2-1)) Nitrocellulose / urethane ink, coating speed 150m / min Laminate (2-1) was obtained in the same manner as laminate (1-1), except that the corona-treated OPP film was changed to a corona-treated PET film (Toyobo E5102, thickness 12 μm), and an aluminum foil (Toyo Aluminum, thickness 7 μm) and an LLDPE film (Mitsui Chemicals Tocello TUX-FCD, thickness 100 μm) were laminated on the printed layer using the adhesive obtained above at a coating speed of 150 m / min in a drying oven (triple oven at 70°C-80°C-90°C).

[0084] (Laminate (2-2)) Urethane ink, coating speed 150 m / min Laminate (2-2) was obtained in the same manner as laminate (1-2), except that the corona-treated OPP film was changed to a corona-treated PET film (Toyobo E5102, thickness 12 μm), and an aluminum foil (Toyo Aluminum, thickness 7 μm) and an LLDPE film (Mitsui Chemicals Tocello TUX-FCD, thickness 100 μm) were laminated on the printed layer using the adhesive obtained above at a coating speed of 150 m / min in a drying oven (triple oven at 70°C-80°C-90°C).

[0085] [Adhesive strength between OPP / VMCPP (initial)] The laminates (1-1) and (1-2) were stored at 40°C for 24 hours to cure the adhesive. Test pieces measuring 15 mm x 300 mm were cut out from the cured laminate, and the adhesive strength (N / 15 mm) between the OPP / VMCPP was measured using a tensile tester at a temperature of 20°C and a relative humidity of 65% at a peel speed of 30 cm / min using a T-peel method. The average value of five test pieces was calculated and evaluated according to the following criteria. A: Adhesive strength is 1.5N / 15mm or more (good) B: Adhesive strength is 1.0N / 15mm or more and less than 1.5N / 15mm (usable) C: Adhesive strength is less than 1.0N / 15mm (not suitable for use)

[0086] [Adhesive strength between OPP / VMCPP (over time)] The laminates (1-1) and (1-2) were stored at 40°C for 24 hours to harden the adhesive, and then further stored in an environment of 40°C and 70% humidity for one month. Using the laminates after storage, the adhesive strength was measured in the same manner as in [Adhesive strength between OPP / VMCPP (initial)], and the average value of five test pieces was calculated and evaluated according to the following criteria. A: Adhesive strength is 1.5N / 15mm or more (good) B: Adhesive strength is 1.0N / 15mm or more and less than 1.5N / 15mm (usable) C: Adhesive strength is less than 1.0N / 15mm (not suitable for use)

[0087] [Adhesive strength between PET / AL / LLDPE (initial)] The laminates (2-1) and (2-2) were stored at 40°C for 48 hours to cure the adhesive. Test pieces measuring 15mm x 300mm were cut out from the cured laminate, and the adhesive strength (N / 15mm) between the PET / VMCPP was measured using a tensile tester at a temperature of 20°C and a relative humidity of 65% at a peel speed of 30cm / min using a T-peel method. The average value of the five test pieces was calculated and evaluated according to the following criteria. A: Adhesive strength is 3.0N / 15mm or more (good) B: Adhesive strength is 1.5N / 15mm or more and less than 3.0N / 15mm (usable) C: Adhesive strength is less than 1.5N / 15mm (not suitable for use)

[0088] [Adhesive strength between PET / AL / LLDPE (over time)] The laminates (2-1) and (2-2) were stored at 40°C for 24 hours to harden the adhesive, and then further stored in an environment of 40°C and 70% humidity for one month. After storage, the laminates were used to measure the adhesive strength in the same manner as in [Adhesive strength between PET / AL / LLDPE (initial)], and the average value of five test pieces was calculated and evaluated according to the following criteria. A: Adhesive strength is 3.0N / 15mm or more (good) B: Adhesive strength is 1.5N / 15mm or more and less than 3.0N / 15mm (usable) C: Adhesive strength is less than 1.5N / 15mm (not suitable for use)

[0089] [Residual solvent] The amounts of residual solvent in the laminates (1-1) and (1-2) were measured and evaluated according to the following criteria. A: Residual solvent amount is 2.0mg / m 2 Less than (good) B: Residual solvent amount is 2.0mg / m 2 More than 3.0mg / m 2 Less than (usable) C: Residual solvent amount is 3.0mg / m 2 Equal to or greater (unavailable)

[0090] [High speed coating ability] The laminate appearance was visually observed for each of the three laminates (1-1), (1-3), and (1-4) with different coating speeds, and those that did not have any appearance defects such as spots were rated as A, those that had only slight spots were rated as B, and those that did have spots were rated as C. The results for the three laminates were combined and evaluated according to the following criteria. A: A rating (good) at a coating speed of 230 m / min. B: At a coating speed of 230 m / min, the coating was rated B or C, but at 200 m / min, the coating was rated A (usable). C: Grade B or C at coating speed of 200 m / min (unusable)

[0091] [Table 1]

[0092] According to Table 1, the adhesive of the present invention shown in the examples showed excellent adhesive strength even without using a silane coupling agent, especially when using ink containing nitrocellulose resin as a binder component. In addition, in high-speed coating of 200 m / min or more, the laminate appearance was excellent and the residual solvent was reduced. In particular, when the acid value of the polyester polyol (B) was in the range of 20 to 50 mg KOH / g and the hydroxy acid was in the range of 0.2 to 0.8 parts, the adhesive strength to the aluminum vapor deposition film was excellent and the high-speed coating property was excellent even when an ink containing nitrocellulose was used. On the other hand, the adhesives of the comparative examples not satisfying the constitution of the present invention could not satisfy all of the requirements for adhesive strength, residual solvent, and high-speed coatability when using ink containing nitrocellulose.

Claims

1. A polyol including a polyether urethane polyol (A) and a polyester polyol (B) having an acid value of 10 to 50 mgKOH / g, a hydroxy acid having two carboxy groups, and a polyisocyanate, the polyether urethane polyol (A) is a reaction product of a difunctional or trifunctional polyalkylene glycol having a number average molecular weight of 100 to 5,000 and an aromatic diisocyanate; the polyester polyol (B) having an acid value of 10 to 50 mgKOH / g is an acid anhydride-modified product obtained by reacting an acid anhydride with a part of the hydroxyl groups of a polyester polyol obtained by reacting a carboxyl group component with a hydroxyl group component, and the content of the polyester polyol (B) is 1.0 to 5.0 parts by mass based on 100 parts by mass of the polyether urethane polyol (A); the hydroxy acid having two carboxy groups is an aliphatic hydroxy acid having 3 to 10 carbon atoms, and the content of the hydroxy acid having two carboxy groups is 0.1 to 1.5 parts by mass per 100 parts by mass of the polyether urethane polyol (A); The reactive adhesive, wherein the polyisocyanate comprises a polyether urethane polyisocyanate which is a reaction product of an aromatic diisocyanate and a polyether polyol, and the content of the polyisocyanate is 50 to 200 mass % based on the polyol.

2. The reactive adhesive according to claim 1, wherein the polyether urethane polyol (A) has a weight average molecular weight of 5,000 to 35,000.

3. 3. The reactive adhesive according to claim 1, wherein the polyester polyol (B) has a number average molecular weight of 500 to 3,000.

4. A laminate having a layer of the reactive adhesive according to any one of claims 1 to 3 between a first substrate and a second substrate.

5. A package using the laminate according to claim 4.

Citation Information

Patent Citations

  • Method of laminating flexible base material by using adhesive not containing organic solvent

    JP1980055863A

  • Adhesive composition for laminated film

    JP1995207246A

  • Aqueous adhesive

    JP2003292933A

  • Adhesive composition

    JP2006306931A

  • Adhesive composition

    JP2006306932A